PUBERTY IN A SAMPLE OF BRAZILIAN SCHOOLBOYS: ONSET AND ANTHROPOMETRIC CHARACTERISTICS - Taciana Carla Maia Feibelmann; Adriana Paula da Silva; Juliana Pereira Pontes Santos; Esthefania Garcia de Almeida; Heloisa Marcelina da Cunha Palhares; Maria de Fátima Borges (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To determine the age of puberty onset in boys and collect anthropometric data of participants at different puberty stages. Methods: This is a cross-sectional study that assessed 430 boys in a random sample representing 48,390 students from public and private schools from the city of Uberaba, Southeast Brazil. The inclusion criteria were males, aged between 5 and 18 years, and absence of previous diseases. Participants and their guardians filled a semistructured questionnaire with questions relevant to their and their parents' puberty. We set the significance at p<0.05 and calculated the 95% confidence intervals. Results: The mean age found in the puberty stage G2 was 11.2±1.8 (95% of participants in stage G2 were 9.2-13.4 years old). Pubarche data showed a mean of age of 11.0±1.6 years (95% of the participants experienced pubarche when they were 8.0-14.0 years old). When compared to the confidence intervals of two classical studies on the subject, our results showed a trend toward earlier pubarche. In addition, the mean age of this event in the children's parents was of 12.1±1.4 years, which was significantly higher than the age of the children's pubarche (p<0.001). Conclusions: These results indicate a secular decreasing trend in pubarche age and an earlier puberty onset. Considering these parameters, is important to design public policies aimed at preventing these early events.